On preemption in discrete and continuous time - Jan-Henrik Steg (Bielefeld University, Center for Mathematical Economics (IMW), 2016)
The seminal work of Fudenberg and Tirole (1985) on how preemption erodes the value of an option to wait raises general questions about the relation between models in discrete and continuous time and thus about the interpretation of its central result, relying on an "infinitely fine grid". Here it is shown that the preemption equilibrium is the limit of the unique symmetric equilibria of the game when reduced to any sequence of grids becoming infinitely fine. Furthermore, additional subgame perfect equilibria using conventional continuous-time mixed strategies are identified.
urn:nbn:de:0070-pub-29022233
Keywords: C61; C73; D21; D43; L12; L13; 330; Preemption; discrete time; continuous time; subgame perfect equilibrium; convergence